2017
DOI: 10.1158/1535-7163.mct-16-0451
|View full text |Cite
|
Sign up to set email alerts
|

Penfluridol Represses Integrin Expression in Breast Cancer through Induction of Reactive Oxygen Species and Downregulation of Sp Transcription Factors

Abstract: It was recently demonstrated the penfluridol inhibited breast tumor growth and metastasis and this was associated with downregulation of α6- and β4-integrins. In this study, we observed the penfluridol induced reactive oxygen species (ROS) and this was the primary mechanism of action. Penfluridol-mediated growth inhibition, induction of apoptosis, and inhibition breast cancer cell migration was attenuated after cotreatment with glutathione (GSH). Penfluridol also downregulated Sp transcription factors Sp1, Sp3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 44 publications
7
36
0
Order By: Relevance
“…Repression of integrins with penfluridol treatment in breast cancer was also shown through reactive oxygen species and Sp transcription factors in a very recent study [16]. It has been reported by several published studies that GLI1 regulates integrins in different cancer models [17, 18].…”
Section: Discussionmentioning
confidence: 91%
“…Repression of integrins with penfluridol treatment in breast cancer was also shown through reactive oxygen species and Sp transcription factors in a very recent study [16]. It has been reported by several published studies that GLI1 regulates integrins in different cancer models [17, 18].…”
Section: Discussionmentioning
confidence: 91%
“…Penfluridol is a long acting oral antipsychotic agent for schizophrenia treatment, widely used in the clinic since 1970 [46]. It has been recently demonstrated to have potent anti-cancer activity for breast cancer [27,30,47], pancreatic cancer [28,48] and glioblastoma [29,49]. A series of characteristics of this drug, such as its in vivo stability, allowing weekly administration to schizophrenia patients, the high potency to cross the blood-brain-barrier, and the anticancer activity, highlight the potential for repurposing this drug for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Penfluridol is a potent, long-acting oral antipsychotic drug long used for schizophrenia, acute psychosis, and Tourette syndrome [23][24][25][26]. Our previous studies have shown the anti-cancer efficacy of penfluridol against breast, brain, and pancreatic carcinoma [27][28][29][30]. However, there is no study on the effect of penfluridol on the tumor vascular microenvironment, especially in clinically relevant doses prescribed for schizophrenia and other psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction between the long non-coding RNA ZFAS1 and miR-150-5p suppresses the expression of Sp1 in epithelial OC cells [95]. An antipsychotic drug, penfluridol, is currently used as an anti-cancer drug since it can downregulate the TFs like Sp1, Sp3, and Sp4 [96]. It was found that penfluridol inhibits cancer cell growth by suppressing expressions of α6and β4-integrins, primarily regulated by the Sp1 along with orphan nuclear receptor 4A1 (NR4A1) [97].…”
Section: Sp1 As a Therapeutic Target In Ocmentioning
confidence: 99%